Improving Function Through Mosque Administration Reform at the Baiturrahman Banda Aceh Mosque - Halimah Halimah; Muhammad Iqbal (Budapest International Research and Critics University, 2019)
Mosque is the center of the activities of Muslims. From there Muslims should design their future, both in terms of DIN Economics, politics, social and the whole joints of life, As its predecessors enable the mosque to its fullest extent.This is because the mosque has the ideal functions as a center of worship and culture of Muslims and have approximately 1100.000 units spread across Indonesia. However, this potential can’t be well applied. Therefore, strategies are needed that can be used to improve function of mosque, one of the strategies that can be done is through administrative reform. One example of a fairly prominent mosque in improving their business functions through administrative reform is mosque of Baiturrahman Aceh. Since the mosque was inaugurated in1612 to present (2019), it had been developed and improved. This study is descriptive qualitative research approach; focus on how the administrative reforms carried out and what are factors supporting and inhibiting the implementation of administrative reform at Baiturrahman Mosque Aceh in improving function.